PERAN KOMUNIKASI, KOMPENSASI DAN GAYA KEPEMIMPINAN TERHADAP SEMANGAT KERJA PEGAWAI DI KEBUN RAYA EKA KARYA BALI - Komang Trisna Sari Dewi (ARTHA SATYA DHARMA, 2022)
This study aims to determine the role of communication on employee morale, the role of compensation on employee morale, and the role of leadership style on employee morale at the Eka Karya Botanical Gardens Bali. The population in this study were all employees of the Eka Karya Bali Botanical Gardens, totaling 68 people. The research method used is quantitative method, the data is obtained by distributing questionnaires to the sample which is then analyzed using multiple regression analysis. The results showed that communication significantly affected employee morale at the Eka Karya Botanical Gardens Bali with a tcount of 15,015. Likewise, compensation has a significant effect on employee morale with tcount of 38.282. Leadership style also has a significant effect on employee morale with a t- value of 20,962.